The Effect of Mental Rotation Training on the Balance and Falling of the Elderly Women with Physical Training Method - Mohammad Taghi Aghdasi; Seyed Hojjat Zamani Sani; Saba Mohammad Alinezhad; Sahand Eslami; Fatemeh Farrokhzad 5 (Allameh Tabataba'i University Press, 2019)
Purpose: The aim of this study was to compare the effect of eight weeks physical and mental rotation training on the balance and falling of elderly women. Method: The present study is a quasi-experimental study with a pre-test, post-test and two-way ANOVA, which is also t-test designed. Tools included: mental rotation questionnaire and functional reach test. The participants included: 36 patients (12 subjects in three groups of physical training, mental rotation and control group) have been randomly selected among the elderly women of an elderly Centre in Tabriz. The training program was administered in two groups of physical training and mental rotation for eight weeks, at three sessions in a week and a group of control with no intervention. For data analysis, the SPSS software, version 21 was used. Results: One-way ANOVA showed, the mean balance among the elderly women was significantly different from the physical training group. The relationship between post-test mental rotation and pre-test physical training was significant at the 0.01 level. Also, the relationship between the post-test mental rotation group and the pre-test mental rotation group was significant at the level of 0.05 and the relationship between mental rotation and balance among elderly women is significant at the 0.01 level, at the end the relationship between mental rotations and falling in the elderly was significant at 0.05 level. Conclusions: The results of this research indicates that the physical training and mental rotation training had a positive effect on the balance of the elderly women and it also showed that the elderly women of the physical training group had more improvement on balance than mental rotation groups. So, this research indicates that, cognitive abilities and movements could be facilitating and effective in this way.